A CRETACEOUS SUPRA-SUBDUCTION OCEANIC BASIN SOURCE FOR CENTRAL PHILIPPINE OPHIOLITIC BASEMENT COMPLEXES: GEOLOGICAL AND GEOPHYSICAL CONSTRAINTS - Dimalanta C.B.; Suerte L.O.; Yumul G.P.; Tamayo R.A.; Ramos E.G.L. (My University, 2006)
The Central Philippines is made up of several Cretaceous oceanic lithospheres that were generated and emplaced in a variety of geologic setting and manner. The Antique Ophiolite Complex exposed along the western side of Central Philippines is associated with blueschists, which suggests tectonic erosion accompanied subduction during its emplacement. Mélanges are associated with the Southeast Bohol Ophiolite Complex and the Cebu ophiolitic rocks suggesting that subduction kneading was a major process during the emplacement of these oceanic fragments. The geology and geochemistry of the Tacloban Ophiolite Complex in Northern Leyte, the Malitbog Ophiolite Complex in Southern Leyte and the dismembered ophiolitic sequence in southern Samar imply that subduction played a role in the generation and emplacement of these Cretaceous oceanic lithospheres. Whole rock major and trace element, along with spinel mineral chemistry, favor a suprasubduction zone origin for these ophiolites. The ophiolites become younger towards the east (present-day geographic setting) indicating that convergence was accentuated by trench jumping. The similarities in the petrologic features, geochemical signatures and ages displayed by these oceanic lithosphere fragments in Central Philippines indicate that they were probably derived from a single Cretaceous oceanic basin which could have been a part of the proto-Philippine Sea Plate.
Keywords: OCCANIC LITHOSPHERES; SUBDUCTION; CRETACEOUS; PHILIPPINES; Mesozoic::Cretaceous; Мезозой::Меловая